Digital Marketing and Consumer Behaviour Towards Purchase Decisions: A Study With Reference To Punjab and Haryana - Kaur, Sumanpreet (My University, 2026)
Digital marketing has become a cost-effective strategy amidst the rapid expansion of online platforms, particularly among digitally native consumers. Anchored in an integrated (Unified Theory of Acceptance and Use of Technology-Theory of Planned Behaviour) UTAUT–TPB cultural framework, this study examines how behavioural and socio-cultural factors, mediated through Digital Marketing Channels (DMCs), influence consumer purchase intentions. Data was collected via a self-designed questionnaire from 600 respondents using Likert scale options, across Punjab and Haryana and analysed using regression analysis, ANOVA, and Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that modern consumer behaviour is predominantly shaped by individual financial circumstances and pragmatic concerns rather than external social or cultural pressures. Although digital marketing channels do not directly affect purchase intentions, they exert a significant indirect influence through enhanced product preference and information search behaviours. Social and cultural factors emerged as robust predictors of purchase intention (path coefficient = 0.490, t = 14.847, p < 0.01), while information search and evaluation also showed a significant positive association (path coefficient = 0.454, t = 12.617, p < 0.01). Product preference notably mediated the relationship between digital marketing channels and purchase intentions, amplifying the effect (path coefficient = 0.151, t = 4.133, p < 0.01), with a significant direct association between digital marketing channels and product preference (path coefficient =0.701, t=34.300, p < 0.01). Theoretically, this research extends technology acceptance models by integrating attitudinal, normative, and cultural constructs within UTAUT and TPB frameworks and articulating a theory of change (ToC) logic model tailored for digital commerce in emerging markets. Practically, the study offers actionable insights for marketers to optimize digital channel strategies within rapidly evolving digital ecosystems.
Keywords: MARKETING; digital marketing; product prefreneces; purchase intentions